Assembly of Disaster Evacuation Signs for Disaster Mitigation at State Vocational School 2, Tangerang City - Aryana Rachmad Sulistya; Kemala Hayati; Tiara Ramadhanti; Muhammad Sulthon Abdussalam; Putu Ayu Cintya Maharani; Kurniawan Fitri Nugroho; Irwan Febry Armansyah (Universitas Muhammadiyah Surakarta, 2026)
Disasters in Tangerang City from 2019-2024 are very diverse, including floods, earthquakes, extreme weather, and landslides and others. Disasters cause losses in terms of infrastructure, loss of life, and other losses. At schools, students, teachers and school employees are at high risk of disaster. One form of disaster mitigation carried out in SMK Negeri 2 Tangerang city is the assembly of signs (equipment) supporting disaster evacuation. The assembly of disaster evacuation support signs aims to support disaster mitigation and reduce losses caused during disasters. (1) Background of the problem: Disaster mitigation at State Vocational School 2 is necessary due to the lack of proper disaster evacuation route signs at all locations. This is being achieved by installing evacuation signs. (2) Objectives: this study aims to examine the assembly of disaster evacuation signs for disaster mitigation and its benefits (advantages) in SMK Negeri 2 Tangerang City. (3) Methods: The method used is direct observation and collaborative method (4) Result : The design of disaster evacuation signs using standard provisions to support disaster mitigation. Assembly of disaster evacuation signs that have been carried out at SMK Negeri Negeri 2 Tangerang City for disaster mitigation include: 1) flat right evacuation route; 2) flat left evacuation route; 3) emergency exit; 4) right evacuation route down; 5) instructions/how to use light fire extinguishers (APAR); 6) evacuation route to the right (plank); 7) evacuation route to the left (plank); and 8) assembly point. The installation of evacuation signs has a positive impact on disaster preparedness and mitigation efforts for SMK Negeri 2 Kota Tangerang. (5) Conclusion : All disaster evacuation signs have been installed and provide many benefits for the academic community of SMK Negeri 2 Kota Tangerang.